Service Quality Analysis to Increase Customer Satisfaction at Milk Tea Coffee - Deepak Kapur (Journal of Current Research In Multidisciplinary, 2023)
This research aims to analyze service quality to increase customer satisfaction. This research uses a quantitative type of research. This research used a population of students and used purposive sampling with 30 respondents. The method for collecting data uses the e-questionnaire method using Google Forms. The data that has been obtained is processed using importance-performance analysis. Based on the research results, it was found that all service quality indicators that support increased satisfaction have negative values. The indicator with the lowest level of performance is the availability of supporting facilities (Q4; -0.933), followed by the level of cleanliness of the outlet (Q3; -0.700), in third place, namely the suitability of the menu served with what is offered (Q10; -0.633), in third place. Fourth is the ease of finding a parking space (Q1: -0.600); fifth is the level of employee service (Q7: -0.533). Followed by the comfort level of the outlet (Q5; -0.467), then in seventh place there is the level of speed of service (Q6; -0.400), then in order of depth, namely the level of knowledge of the product from the waiter (Q8; -0.400), then continued with the communication ability to answer questions. from service (Q9; -0.367) and finally, namely, interior beauty (Q2; 0.333).